Contribution to the Systematic Study of the Ornamental Flora of Gorée Island (Dakar-Senegal) - Birane Dieng; Fatou Kine Gueye; Gnima Sagna; Jules Diouf; Ndongo Diouf; Alioune Gaye; Ndeye Fatou Dieng Fall; Penda Lo; Samba Laha KA; Alassane Diouf; Kandioura Noba; Mame Samba Mbaye (European Scientific Journal, ESJ, 2026)
Gorée Island, located approximately 4.5 km off the coast of Dakar, is both an island in the North Atlantic Ocean and one of the 19 boroughs of Senegal's capital city. This emblematic site has been widely studied in fields such as archaeology, geology, history, and tourism. However, its ornamental flora has received very little scientific attention. This is particularly concerning given that recent decades have been marked by the depletion of its natural resources due to numerous human activities combined with urban expansion and climate change. It is therefore crucial to improve scientific knowledge of Gorée Island's ornamental flora to support sustainable and participatory management. This study, conducted in September 2021, aims to contribute to a broader understanding of Gorée's ornamental flora. More specifically, this study aims to establish the taxonomic, biological, and chorological profiles of the ornamental flora of Gorée. The methodological approach consisted of conducting a field survey in the three gardens (Canary Garden, Public Garden, and Succulent Plant Garden) and the flowerbeds of the municipality. The results showed that 55 plant species belonging to 49 genera, grouped into 31 families, were identified. Of these species, 36 are already listed in the flora of Senegal, while the remaining 13 have not been recorded and could be introduced to Senegal. This flora is composed exclusively of angiosperms, with three dominant families: Apocynaceae (9.09%), Acanthaceae (7.27%), and Asparagaceae (7.2%). In terms of biological types, Phanerophytes are the most represented (50.91%), followed by Chamaephytes (20%). Chorologically, the flora is dominated by pantropical species, which account for 34.55% of the species mentioned, compared to 21.82% for other African-American species.Conclusion and application: This work has allowed us to characterize the ornamental flora of Gorée Island. Indeed, the structure of the flora, as well as its taxonomic, biological, and chorological spectra, has been determined. The results of this study can be used to develop tools for taxon identification (identification key).